Antibacterial Activity of Green Sirih (Piper betle L) Extract towards Food Pathogens - Suliantari .; B S L Jenie; A Apryiantono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2008)
Green sirih (Piper betle L) extract were prepared using water, athanol and ethyl acetate extractionof the dried material. The extracts were tested for their antibacterial activities against Escherichia coli, Salmonella Typhimurium, Pseudomonas aeruginosa, Staphylococcus aureus, Bacillius cereus and Listeria monocytogenes. At concentrations10-50% the extracts effectively inhibited the growth of all tested bacteria as shown by the clear zones which varied from 7 to 24 mm, while the minimum inhibitory concentration (MIC) varied from 0.1 to 1 %. E. coli, S. Typhimumirum and S. aureus were more resistance to the green sirih extracts than other tested bacteria. The result showed that in general, ethanol extraction produced the best extract with strong antibacterial activities against E. coli and S. aureus. Analysis of the extract components with GC-MS revealed that sirih extract contained phenol, chavicol, eugenol, caryophylene, cylene, chalarene and others. Key words: Green Sirih (Piper betle L), bioactive compound, antibacterial.